Optical coherence tomography angiography: Technical principles and clinical applications in ophthalmology - Ahmed M Hagag; Simon S Gao; Yali Jia; David Huang (Taiwan Journal of Ophthalmology, 2017)
Optical coherence tomography angiography (OCTA) is a functional extension of OCT that provides information on retinal and choroidal circulations without the need for dye injections. With the recent development of high-speed OCT systems and efficient algorithms, OCTA has become clinically feasible. In this review article, we discuss the technical principles of OCTA, including image processing and artifacts, and its clinical applications in ophthalmology. We summarize recent studies which qualitatively or quantitatively assess disease presentation, progression, and/or response to treatment.